2014
DOI: 10.4236/health.2014.620321
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Recovery-Focused Program for Stress Management in Women<br/>—An Exploratory Study

Abstract: Current research indicates that stress problems primarily could be conceptualized as deficiencies in recovery and recuperation between stress periods. Accordingly, interventions should put more emphasis on this aspect. A group based intervention program focusing exclusively on recovery behavior in everyday life was evaluated in this quasi-experimental, waiting-list control group study, where the control group was also treated in a second phase. Thirty-two self-referred female subjects, considering themselves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…This is an important finding because it may help us select measurement tools for the examination of job stress recovery experiences. For example, following an intervention, Lisspers et al (2014) found that changed levels of "recovery behaviour" were associated with changed levels of burnout in a subclinical sample. Thus, recovery-focused interventions might be a suitable approach in both treatment and prevention of burnout and valid measures of recovery experiences could add understanding to recovery processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding because it may help us select measurement tools for the examination of job stress recovery experiences. For example, following an intervention, Lisspers et al (2014) found that changed levels of "recovery behaviour" were associated with changed levels of burnout in a subclinical sample. Thus, recovery-focused interventions might be a suitable approach in both treatment and prevention of burnout and valid measures of recovery experiences could add understanding to recovery processes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, relaxation, describes the experiences of low activation in the organism (Sonnentag et al, 2017;Stone, Kennedy-Moore, & Neale, 1995). Relaxation can stop the prolongation of harmful physiological stress responses and enable recovery processes to occur (Brosschot, Pieper, & Thayer, 2005;Geurts & Sonnentag, 2006;Lisspers, Almén, & Sundin, 2014).…”
mentioning
confidence: 99%
“…The treatment has been included in three randomized trials as face‐to‐face treatment (present study: Salomonsson et al ., ), stepped care with guided self‐help and face‐to‐face treatment (Salomonsson et al ., ), and as an Internet‐based treatment (Lindsäter et al ., ). The treatment is based on a model assuming that these disorders are maintained by a deficit of recuperation (Geurts & Sonnentag, ; Lisspers, Almén, & Sundin, ) that can be caused by for example difficulties to relax, extensive rumination, or aversive consequences of relaxing (e.g., a person may feel shame or guilt if taking a rest instead of working or helping friends or family). The main components were psychoeducation regarding stress, practicing relaxation, scheduled recuperation, behavioural activation including valued living across a person’s different life areas, and exposure to break fear avoidance patterns.…”
Section: Methodsmentioning
confidence: 99%
“…The present thesis focuses specifically on deficits in recovery as a central factor in the genesis and maintenance of stress-related problems [34][35][36] (although numerous other theories of the potentially aversive consequences of prolonged exposure to non-traumatic stressors exist).…”
Section: Exhaustion Disordermentioning
confidence: 99%
“…No evidence-based treatments exist for exhaustion disorder (ED). The treatment protocol used in the present thesis was developed by our research group, and is based on a model highlighting deficits in recovery, particularly recuperating activities but also associated with sleep, as central maintaining factors of exhaustion [34][35][36] .…”
Section: Change Processes In Cbt For Exhaustion Disordermentioning
confidence: 99%